Computer-Based Facility Management in Abuja, FCT: Adoption, Benefits, and Challenges Among Facilities Management Professionals - David, Adekunle (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2025)
This study assesses the adoption of Computer-Based Facility Management (CBFM) in Abuja, Federal Capital Territory (FCT), Nigeria, focusing on its benefits and challenges among facility management professionals. A mixed-methods approach involving surveys and semi-structured interviews was employed to collect data from facility managers, maintenance personnel, and estate surveyors. The findings reveal that CBFM adoption has significantly improved operational efficiency, data management, predictive maintenance, and sustainability practices. Benefits include automation of processes, enhanced decision-making, optimized space utilization, and reduced operational costs. However, the implementation of CBFM systems is hindered by high setup costs, inadequate infrastructure, a shortage of skilled personnel, and resistance to change. Limited awareness and training gaps further contribute to its underutilization. Despite these challenges, the study observes a growing interest in CBFM tools in Abuja’s facility management sector. Recommendations include targeted training programs, awareness campaigns, financial support mechanisms, and stronger collaboration between stakeholders to enhance adoption. The study contributes to the discourse on digital transformation in facility management and provides actionable insights for improving built environment service delivery in rapidly urbanizing cities.